AN ANALYSIS OF STUDENTS’ ERROR IN PERCEPTION OR PRODUCTION IN PRONOUNCING ENGLISH SOUNDS WHICH HAVE DIFFERENT DISTRIBUTIONS WITH THEIR NATIVE LANGUAGE - Biantoro, Ryan; Sisbiyanto, Amir; ., Suprapto (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2018)
This paper is written based on the error analysis on perception or production inpronouncing English sounds which have different distributions by the students ofSMP N 2 Demak in Academic Year of 2015/2016. The study was aimed to describeand to explain the most common problems faced by the students in learning Englishfinal voiced stops [b, d, g]. This study is using qualitative approach. The populationof the study was the eight grader students of SMP N 2 Demak. The total numbers ofthe population used in this research are 310. Random sampling technique was usedto get the sample. The data of this study was obtained from listening and speakingtests. The result of those tests were used as the source of data collection. Then, theresult was interpreted by using Tinambunan‟s criterion grading. In perception test,the error proportion of the 30 students was 6,07% while in the production test, theerror proportion was 28,2% out of 30 students. Based on the results, it is concludedthat the students were considered exellent in perceiving but fair in pronouncing finalvoiced stops [b, d, g].